Pastoral Psychology and Pastorology: Interdisciplinary Boundaries and Heuristic Opportunities (Forum Theologicum Sardicense, 2025)
The article examines the role of pastoral psychology and soul care within both theological and secular studies. The author employs modern scientific language and terminology while preserving their original meaning, and integrates these with patristic literature and traditional pastoral psychology.
Keywords: Social Work; Religious Studies; Pastorology; Pastoral Psychology; Practical Theology